PENGARUH PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MPASI) DINI TERHADAP KEJADIAN DIARE DAN PERTUMBUHAN BAYI 6-12 BULAN - , Tunjungsari Ratna Utami, Prof.dr. Purnomo Suryantoro, DTM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Back ground: WHO has revised global recommendation on breastfeeding as soon as possible one hour after birth and exclusive breastfeeding until 6 months old. After that, babies are given complementary feeding while breastfeed should be continued until 2 years. Early complementary feeding has been associated with increased morbidity from infectious diseases and linear growth faltering. Objective: examined the effects of early complementary feeding on infant growth and diarrhea Methods: the samples of this study are healthy infants that lived at Ngaglik, Sleman, Yogyakarta. Infants were followed since they were 6 months old until 12 months old and they were been divided into early complementary feeding and no. We measure the length, weight, head circumference, and incidence of diarrhea. Results: there were 174 infants that we observed, 50 (28,8%) were given complementary feeding at 6 months old and 124 infants (60,9%) were given complementary feeding before 6 months old. The increasing of weight, length, and head circumference in the group of infants with early complementary feeding are lower than the group of infants with 6 months complementary feeding, but not statistically significant, p>0,05 (weight 1027 versus 980,2 g